Using 3D Echo-based Modeling to Quantify in Vivo Ventricle Material Properties: A Multi-patient Study. (2015) - Fan, Longling; Yao, Jing; Yang, Chun; Xu, Di; Tang, Dalin
Abstract: Methods to quantify ventricle material properties noninvasively using in vivo data are of great importance in clinical applications. Echo image data were acquired from ten people, five patients with myocardial infarction (Group 1) and five healthy volunteers as control (Group 2). 3D finite element models were constructed to obtain ventricle stress and strain conditions. Material stiffening and softening were used to model ventricle active contraction and relaxation. Our results indicated that Group 2 had much greater systole-diastole material stiffness variations. This initial study indicated that our modeling approach has the potential to determine in vivo ventricle material properties, which in turn could lead to methods to infer presence of infarct from LV contractibility and material stiffness variations.